Genetic resources of pulse crops in India: An overview - Rana, J. C.; Gautam, N. K.; Gayacharan, 1; Singh, Mohar; Yadav, Rashmi; Tripathi, Kuldeep; Yadav, S. K.; Panwar, N. S.; Bhardwaj, Rakesh (The Indian Journal of Genetics and Plant Breeding, 2017)
India is rich in genetic diversity of major pulse crops, but the productivity and the production of pulse crops remains low compared to the world and hence, there is a need to enhance the utilization for increasing the production. Major pulse species for which genetic diversity is occurring in India include Vigna,Cajanus,Cicer,Pisum,Lens,Phaseolus and few minor pulses such as Macrotyloma, Canavalia, Lathyrus, Vicia, Mucuna, Moghania and Rhynchosia etc. National Bureau of Plant Genetic Resources (NBPGR) is the nodal institute for the management of plant genetic resources in India. It has assembled 70,000 accessions of different pulse crops majoring Cajanus cajan, Cicer arietinum, Phaseolus vulgaris, Pisum sativum, Vigna mungo, Vigna radiata, Vigna umbellata, Vigna unguiculata, Vicea sp. and Lens sp. through collection and introduction from India and from >70 other countries of the world. Several pests of quarantine significance have been identified and salvaged from the exotic germplasm. The ex situ base collection at NBPGR conserve 64,744 accessions of 20 genera and 61 species of pulses. This germplasm has been characterized for agro-morphological, quality and biochemical traits, biotic and abiotic stresses for identifying trait-specific reference sets and 28 catalogues describing about 45,000 accessions of 14 pulse crops. A total of 121 accessions of various pulse crops have been registered as unique/potential donors. Core and mini cores have been developed in chickpea, pigeonpea, common bean, mungbean, adzuki bean, cowpea, lentil, moth bean and pea both nationally and internationally. Wild species of pulse crops have been utilized for transferring desirable traits into cultivated species. Application of modern tools and technologies of molecular biology will accelrate the process of gene transfer for improvement of pulse crops.